Night entertainment venues comply poorly with the smoke-free law in Chile - Armando Peruga; Marcela Fu; Xaviera Molina; Esteve Fernández (Elsevier, 2021)
The initial high level of compliance with the Chilean comprehensive national smoke-free law in 2013 is fading, particularly in the hospitality sector. This paper draws attention to how using a simple and low-cost surveillance inquiry may help focus on the use of scarce inspection resources to improve compliance with the law in the hospitality sector. We conducted a cross-sectional assessment of second-hand smoke exposure in night entertainment venues in Santiago, Chile, by measuring particulate matter of less than 2.5 μm (PM2.5). Smoking where prohibited by law was observed in 36% of the venues visited. Venues where smoking was spotted at the time of the observation had a median PM2.5 concentration 13 times higher than background concentration on the street. The study shows that a targeted approach for inspection to find pockets of venues with suboptimal compliance is feasible and affordable. Resumen: El alto nivel inicial de cumplimiento de la Ley integral chilena de ambientes libres de humo de 2013 se está desvaneciendo, particularmente en el sector de la restauración. Este documento muestra cómo una encuesta de vigilancia simple y económica puede ayudar a mejorar el uso de recursos de inspección escasos para mejorar el cumplimiento de la ley en dicho sector. Se realizó una evaluación transversal de la exposición al humo de tabaco ajeno en locales de entretenimiento nocturno en Santiago, Chile, midiendo el nivel de partículas menores de 2,5 μm (PM2.5). En el 36% de los locales visitados se fumaba donde lo prohíbe la ley. Los locales en los que se fumaba tenían una concentración mediana de PM2.5 13 veces mayor que la concentración en la calle. El estudio muestra que una vigilancia enfocada en la inspección de lugares con cumplimiento subóptimo es factible y asequible.